Antiinflamatory effect in mice of extracts of Calceolaria tripartita R & P, compared phytochemical with the hydroalcoholic extract of Calceolaria melissifolia "Bentham" - Mayhuasca, Olinda (2007)
The studies of investigation were orientated to verify the antiinflammatory activity, attributed tor the popular use, in the District of Huancayo's Pilcomayo Provincia, Department of Junín, of the species Calceolaria tripartita R and P. One worked with the air parts leafes of the plant belonging to the Kind Calceolaria and to the Family Scrophulariaceae. They were done extracciónes constant by Soxhlet. There was realized a preliminary screening fitoquímico of the etanolic extract in which it was situated: alkaloids, catequins, steroids, triterpenoids, flavanoids, saponins and tannins. From equal form one came with the diclorometanic extract, being: essential oils, oily acid, rumarins, s teroids and triterpenoids. The pharmacological activity was realized according to the method of the ear edema induced by oil of croton in mice. Evaluating the antiinflammatory activity of the etanolic extract and diclorometanic to adose of 1 mg/ear, opposite to medicaments of known antiinflammatory activity since they are the dexametasona acetate and the indometacina, which were used to a dose of 0,1 mg/ear and 0,5 mg/ear respectively. Both extracts possess antiinflammatory activity, presenting major activity the etanolic extract. On the other hand on having realized the antimicrobial study of the watery extract of the Calceolaria's melissifolia Bentham Subsp. Pseudoscabra (Edwin) Molau., air parts, proceeding from Celendín's province, Cajamarca's department constituented for fenolic compounds type flavonoids Di that three isolated and identified as 7,4 '-di-O-alquil-3,5,3 trihidroxiflavonol; 5,7,4 '-tri-O-alquil-3 " 5'dihidroxiflavanone and 5,7,4- trihidroxiflavone by means of chromatographic and spectroscopic methods UV-Visible in methanol and with reagents of displacement, in addition to tannins and steroids; one was that inhibits the growth Di Staphylococcus aureus and a partial inhibition of the growth of Escherichia coli.